Morphological assessment of the Cambrian trilobites Oryctocephalus indicus (Reed 1910) from China and Oryctocephalus 'reticulatus' (Lermontova 1940) from Siberia. (27th August 2016) - Esteve, Jorge; Zhao, Yuanlong; Peng, Jin
Abstract: Oryctocephalus indicus is a widespread trilobite species described from the lower–middle Cambrian (provisional Cambrian Stage 5) of south China, North Korea, India, USA and possibly North Greenland. Principal component analysis (PCA) and thin‐plate splines (TPSs) based on a pooled sample of 359 specimens from four sections in the Guizhou Province, south China, demonstrated that the shape of this species is very constant, and only a small difference is detected in specimens from deeper part of the basin. Most of the variation is taphonomically controlled, and only the specimens from Sanwan Section show a modest natural difference due to a slightly different depositional environment. A comparison between the Chinese specimens and Oryctocephalus 'reticulatus' from the Molodo Section, Siberia, has been carried out. PCA and TPS show that O .  'reticulatus occupies the same morphospace of O. indicus . However, the canonical variates analysis and the analysis of similarities detect small differences between the Siberian and Chinese populations, indicating a minor geographical variation caused by different environmental settings. The ontogenic variation is also described from early meraspids to holaspids. The most substantial changes take place during the first period of the early meraspid development, in which the glabella changes from a bell‐like shape to a cylindrical shape. The ocular ridge changes from poorly defined in early meraspid to well developed in late merapids. The results indicate that O .  'reticulatus' is a junior synonym of O. indicus, suggesting that the base O. indicus of Siberia can be correlated with the O. indicus Zone of south China.